2015
DOI: 10.1016/j.micres.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cyanobacterial inoculation on the culturable microbiome and growth of rice

Abstract: Rice plants are selective with their associations with bacteria that are beneficial for growth, nutrient uptake, exhibit induced resistance or antagonism towards pathogens. Cyanobacteria as bioinoculants are known to promote the growth and health of rice plants. The present investigation was aimed at understanding whether and how cyanobacterial (Calothrix elenkinii) inoculation influenced the rice plant growth and the culturable bacterial populations and identifying the dominant culturable "microbiome" members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(47 citation statements)
references
References 54 publications
3
40
0
1
Order By: Relevance
“…Therefore, they could be widely-used as excellent natural bio-fertilizers and in reclamation of the nutrients-poor desert soils of El-Farafra Oasis. In agreement with these results, recent contribution of Priya et al (2015) showed that there is a significant increase in rice plant growth inoculated with Calothrix elenkinii. Goyal (1993) confirmed that Scytonema grows well on the soil surface and fixes more nitrogen than the most Egypt.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, they could be widely-used as excellent natural bio-fertilizers and in reclamation of the nutrients-poor desert soils of El-Farafra Oasis. In agreement with these results, recent contribution of Priya et al (2015) showed that there is a significant increase in rice plant growth inoculated with Calothrix elenkinii. Goyal (1993) confirmed that Scytonema grows well on the soil surface and fixes more nitrogen than the most Egypt.…”
Section: Resultssupporting
confidence: 86%
“…This is because Rhizobium fixes atmospheric N [49,63] in root nodules (active root nodules were found in most plants treated with Rhizobium), which compensated for a portion of the chlorophyll degradation from salt stress. Microbial inoculations are also reported to increase the chlorophyll content of plant leaves [64,65].…”
Section: Analysis Of Leaf Chlorophyll Content (Spad Readings)mentioning
confidence: 99%
“…Two strains of Gluconacetobacter diazotrophicus isolated from endorhizosphere of sweet sorghum (Acd1 and Acd2) were tested for their plant growth potential and nitrogen-fixing ability along with a reference strain obtained from Brazil (Pal3) under green house and field conditions with sweet sorghum cultivar PC 121 in the presence of fertilizer nitrogen (20 and 40 kg N ha -1 ) applied in the form of isotopically labelled ammonium sulphate [( 15 (NH 4 ) 2 SO 4 ] (Sahai et al, 2015). Priya et al (2015) studied the influence of cyanobacterial inoculation on the culturable microbiome and growth of rice. Many reports on the inoculation of PGPR along with Rhizobium were published (Tsigie et al, 2011).…”
Section: Plant Microbe Interactionsmentioning
confidence: 99%